Isolated sphenoid sinus opacifications: a systematic review and meta‐analysis. Issue 12 (12th October 2017) - Moss, William J.; Finegersh, Andrey; Jafari, Aria; Panuganti, Bharat; Coffey, Charles S.; DeConde, Adam; Husseman, Jacob
Abstract : Background: Isolated sphenoid sinus opacifications (ISSOs) represent a relatively uncommon disease with the potential for serious complications. To better understand this disease, we performed a systematic review to further characterize the underlying pathologies, associated symptoms, and treatment outcomes of patients with ISSOs. Methods: A systematic review of ISSO case series was performed utilizing the Medline, Embase, Web of Science, and Cochrane databases in accordance with guidelines established by PRISMA (Preferred Reporting Items for Systematic Reviews and Meta‐Analyses). Data of interest included disease pathology, associated symptoms, and treatment outcomes. Results: Of the initial 1051 hits from the 4 databases, 17 articles, with a combined 1133 ISSO patients, were ultimately included in the review. On a weighted analysis, the underlying pathologies were classified as chronic rhinosinusitis without nasal polyps (CRSsNP) (28.3%), mucoceles (20.3%), fungal sinusitis (12.5%), malignant neoplasms (7.7%), intracranial lesions (7.0%), benign neoplasms (5.7%), chronic rhinosinusitis with nasal polyps (CRSwNP) (3.4%), and other lesions (4.7%). Cranial neuropathies were present in 16.3% (95% confidence interval [CI], 10.1‐22.5%) of ISSO patients. A favorable surgical complication rate of 1.5% (95% CI, −0.1% to 3.2%) was found in patients undergoing surgery for an ISSO. Conclusion: ISSOs are caused by diverse pathologies. Given the considerable rates of neoplastic disease and cranial neuropathies, patients affected by an ISSO should be monitored closely and treated aggressively. Prompt surgical intervention, with either diagnostic or therapeutic intent, is often indicated.